Devaluation and after : vicissitudes of the Fourth plan - Iyengar, S. Kesava (London : Asia Publishing House, 1970)
This book discusses the devaluation of the Rupee in the fourth plan (1969 - 1974. It discusses the economic situation of india following the devaluation.
Includes index
Library has vol. 1
osc 21/2/17
Loans
Keywords: Economic policy; Devaluation of currency; Finance; India